Seasonal variation of carbonaceous PM2.5 in an Istanbul traffic site - AKKOYUNLU, BÜLENT OKTAY; TAYANÇ, METE; FLORES RANGEL, ROSA MARIA (TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP, 2020)
The seasonal variation of fine carbonaceous aerosol was evaluated in an urban traffic site in Istanbul. PM2.5 samples were collected on selected days during four seasons between Jan 2017-Jan 2018. Daily PM2.5 concentrations were obtained experimentally by the gravimetric method in Besiktas, while hourly concentrations were obtained from the Air Quality Monitoring Network of Istanbul in Catladkap, Silivri, Kathane, and umraniye. Organic carbon (OC) and elemental carbon (EC) concentrations were determined by a thermo-optical carbon analyzer for samples collected in Besiktas. The 24-h US-EPA air quality standard of 35 mu g m(-3) was exceeded 13, 25, 41, 42, and 57% of the time in Catladkap, Silivri, Kathane, umraniye, and Besiktas, respectively. These exceedances occurred mainly during the fall and winter owing to a combination of emissions from fuel combustion for residential heating, traffic and industry, and poor air dispersion due to weak atmospheric motion and low mixing heights. Average OC concentrations ranged as 6.62-7.32 mu g m(-3) during spring and summer, and 13.76-14.1 mu g m(-3) during fall and winter. The OC concentrations observed in this work during the summer and winter were 2-4 and 3-6 times higher than concentrations observed in the USA and Europe, respectively. The EC concentrations did not show considerable seasonal variation, with values between 2.16 and 3.26 mu g m(-3). EC concentrations in Besiktas were 7 and 9 times higher than concentrations observed in the USA and Europe, in order. Results obtained in this study could be helpful for future implementation of policies and strategies to reduce emissions from combustion sources in order to comply with the air quality standards.
Keywords: Organic carbon; Elemental carbon; Air pollution; Fine particulate matter; Megacity; OC/EC; Turkey; DUST TRANSPORT; PM10; QUANTIFICATION; TURKEY